Pencegahan Resiko Penularan HIV/AIDS dengan Edukasi Stop Free Sex pada Remaja di SMA Negeri 1 Ciamis - Lenna Mahdalena; Adi Yusuf Attaziri; Hana Yuliani; Cita Rahayuningsih; Nissa Dwi Andaka; Tia Setiawan; Nazwari Febrian (Yayasan Inspirasi El Burhani, 2022)
Introduction: Adolescents are a group that is physically and psychologically vulnerable to HIV infection. Changes in adolescents result in a high desire to try new things, so that adolescents become the main focus of efforts to overcome the spread of the HIV-AIDS virus (Veronika, et al, 2012). Adolescent knowledge about HIV/AIDS prevention is very important, one of the roles of youth here is to seek information related to HIV-AIDS transmission and how to prevent it. Objective: Can improve the quality of education and knowledge of students about HIV-AIDS. Method: The research design used qualitative research methods by observing directly the participant's response to the material presented by the teacher involving 35 students of SMA Negeri 1 Ciamis. Result: Knowledge and understanding is one of the factors in preventing the risk of HIV-AIDS infection in adolescents. Before the counseling was conducted, the presenter asked the participants questions related to HIV-AIDS. 3 participants answered correctly, but the problem faced was that some participants did not know the process of transmission and how to prevent HIV-AIDS, because before delivering the material the participants did not know information about HIV-AIDS. The results of observations before and after the participants' knowledge extension activities increased. Conclussion: The implementation of activities in general went smoothly and received appreciation from the school, especially the principal. After counseling, knowledge increases and gives good responses and answers the questions given correctly.